2001
DOI: 10.4049/jimmunol.167.2.827
|View full text |Cite
|
Sign up to set email alerts
|

CD28 Signaling Augments Elk-1-Dependent Transcription at the c-fosGene During Antigen Stimulation

Abstract: Untransformed CD4+ Th1 cells stimulated with Ag and APC demonstrated a dependence on B7- and CD28-mediated costimulatory signals for the expression and function of AP-1 proteins. The induction of transactivation by the c-fos gene regulator Elk-1 mirrored this requirement for TCR and CD28 signal integration. c-Jun N-terminal kinase (JNK) (but not extracellular signal-regulated kinase or p38) protein kinase activity was similarly inhibited by neutralizing anti-B7 mAbs. Blockade of JNK protein kinase activity wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 66 publications
1
27
0
1
Order By: Relevance
“…Interestingly, the function of c-Jun can be enhanced by CD28 activation via JNK-dependent phosphorylation (11). c-Fos protein levels also vary greatly during the activation of T cells, depending on the strength of CD28 costimulatory signaling (4). Therefore, an increase in Fos gene expression may mediate at least part of the ability of CD28 costimulation to enhance AP-1-dependent transactivation.…”
Section: Ndividual Resting Cd4mentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, the function of c-Jun can be enhanced by CD28 activation via JNK-dependent phosphorylation (11). c-Fos protein levels also vary greatly during the activation of T cells, depending on the strength of CD28 costimulatory signaling (4). Therefore, an increase in Fos gene expression may mediate at least part of the ability of CD28 costimulation to enhance AP-1-dependent transactivation.…”
Section: Ndividual Resting Cd4mentioning
confidence: 99%
“…ϩ Th cells, we previously demonstrated that during stimulation with Ag, interactions between the B7 molecules CD80 and CD86 on the APC and the CD28 receptor are necessary for optimal transactivation by Elk-1, a NF that binds constitutively at the SRE (4). In this case, JNK appeared to mediate the costimulatory effects of CD28 on Elk-1 function.…”
Section: Ndividual Resting Cd4mentioning
confidence: 99%
See 2 more Smart Citations
“…AP components can be activated through a direct phosphorylation of c-Jun at its N-terminus by JNK (Derijard et al, 1994) or an enhanced transcription of c-Jun by ERK and p38 MAP kinase (Han et al, 1997). Additionally, c-Fos protein expression is induced by ERK or JNK in response to growth factors or CD28 signaling (Li et al, 2001). AP-1-regulated genes include important regulators of invasion, metastasis, proliferation, and survival.…”
Section: Introductionmentioning
confidence: 99%